Strategi Pendampingan dalam Pengembangan Usaha Kelompok Perhutanan Sosial di Kabupaten Merangin Provinsi Jambi - Reinold Tampubolon; Fikarwin Zuska; Agus Purwoko (Jurnal Serambi Engineering, 2022)
The social forestry groups in Merangin Regency, Jambi Province consisting of LPHD Lubuk Birah, LPHD Lubuk Beringin dan LPHD Rio Kemunyang are the groups that have been assisted by social forestry assistance. The business in these groups is underdeveloped as indicated by unavailiability of market access, limited capital, weak institutionalism, etc. The objective of this research is to discover strategy of assistance in social forestry groups business development in the 3 (three) aforementioned groups. The data are collected by conducting in-depth interview, observation, and Focus Group Discussion (FGD), also by distributing questionnaires. They are analyzed by using SWOT analysis with Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS). Based on the SWOT analysis, it is found that the position of assistants is at quadrant IV (defensive strategy) which indicates that it is in unfavorable position where weakness and threat are more serious than its strength and opportunity. The strategy of assistance applied today is on increasing capacity of the assistants in business development, conforming outcomes of groups business with market needs, increasing intensity of effective communication and atmosphere with the groups, consolidating strength of the groups and improving communication with government and authorities to encounter threats of land clearing, increasing motivation of assistants, and living in the location when providing assistance.